2023
DOI: 10.3389/fpubh.2023.1132751
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of recommended vaccinations during pregnancy: a cross-sectional study in Southern Italy

Abstract: BackgroundVaccine administration is a recommended, safe, and effective measure to protect pregnant women against vaccine-preventable diseases (VPDs). Despite available guidance, maternal immunization rates for vaccination against influenza and with the reduced antigen content tetanus-diphtheria-acellular pertussis vaccine (Tdap) in Italy remain incredibly low. The primary goal of the study was to explore what Italian pregnant women knew about VPDs and immunization during pregnancy and what factors affected the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 49 publications
(31 reference statements)
0
13
0
Order By: Relevance
“… 16 , 25 - 27 Despite previous studies have confirmed that vaccination is the safest and most effective method for preventing flu, 3 - 5 concerns about serious vaccine-related side effects and underestimating the risks of severe adverse outcomes during pregnancy still contribute to vaccine hesitancy, in turn, leads to reluctance in getting vaccinated. 28 - 31 A cross-sectional multicenter study in Italy assessed pregnant women’s knowledge, beliefs, and misconceptions about vaccines. The study results showed that only 9% of women completely believed in the safety of vaccinations and almost 20% of women had misconceptions or lack of knowledge about flu vaccinations during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 16 , 25 - 27 Despite previous studies have confirmed that vaccination is the safest and most effective method for preventing flu, 3 - 5 concerns about serious vaccine-related side effects and underestimating the risks of severe adverse outcomes during pregnancy still contribute to vaccine hesitancy, in turn, leads to reluctance in getting vaccinated. 28 - 31 A cross-sectional multicenter study in Italy assessed pregnant women’s knowledge, beliefs, and misconceptions about vaccines. The study results showed that only 9% of women completely believed in the safety of vaccinations and almost 20% of women had misconceptions or lack of knowledge about flu vaccinations during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that those who expressed concerns about potential adverse events for the unborn child from vaccine received during pregnancy were significantly less willing to receive the influenza vaccine (OR = 0.76). 30 From the aforementioned literatures, it is evident that unrealistic perceptions of risk can be associated with barriers that might influence the decision to vaccinate. Therefore, training women to trust accurate healthcare professional information and advice is crucial for making informed choices and increasing vaccine uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evolving population knowledge, attitude, and perception of vaccination effects also played a role, as positive intention in vaccination meant a higher vaccine coverage in the following months, and therefore impacted on COVID management [ 64 , 65 ]. As is known, vaccine hesitancy played an important role in COVID, even more than what is expected for other type of pathogens; such behavior impacts on disease spread and consequent drug prescription attitudes on the territory, and this all has a foreseeable impact on hospital demand [ 66 68 ]. In particular, antibiotic over prescription (by all types of health personnel) is constantly been linked with the occurrence of antimicrobial resistance, and thus with more difficulties in patient care management and further hospitalization increase [ 69 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cost of research and development, manufacturing, quality control, and distribution can contribute to the high prices associated with certain vaccines. This can limit accessibility, particularly for marginalized communities or countries with limited healthcare resources ( 109 ). In addition, while vaccines generally elicit robust immune responses, there can be instances where the immune response is not as strong as desired.…”
Section: Vaccines Based On Phagesmentioning
confidence: 99%